Time-resolved infrared difference spectroscopy in cells: Response of the basic region leucine zipper of aureochrome - Goett-Zink, Lukas; Baum, Eileen; Kottke, Tilman (Frontiers in Physics, 2023)
Aureochromes are light, oxygen, voltage (LOV) proteins and central blue-light receptors in algae acting as light-gated transcription factors. The C-terminal LOV domain mediates blue-light recognition and the basic region leucine zipper (bZIP) domain binds a specific DNA motif as effector. LOV domains from aureochromes have been successfully applied in optogenetic tools. The light-induced response of aureochromes has been studied by a variety of biophysical techniques, but the mechanism of signal progression from LOV to bZIP remains unclear. We studied the bZIP-LOV module of aureochrome1a from the diatom Phaeodactylum tricornutum using time-resolved rapid-scan FTIR difference spectroscopy. Time-resolved difference spectra of bZIP-LOV in vitro revealed a time constant of 5 s for the formation of a light state dimer of the LOV domains and the concomitant loss of a-helical elements in the bZIP domain. To verify these observations in a near-native environment, in-cell infrared difference spectroscopy (ICIRD) was extended from a steady state to a time-resolved technique using LOV domains in bacterial cells. We established a time-resolved in-cell method with a resolution of 7.6 ms after the laser pulse. Using this technique, the response of bZIP-LOV was followed in living bacterial cells and the light-induced partial unfolding of bZIP was confirmed to take place in cells in a similar time range as in vitro. These results provide structural and kinetic insights into the signaling mechanism of aureochromes. The slow response points to an association of LOV to bZIP in the dark state prior to activation.